Microplastics in the digestive tract of two commercially important marine fish species from the Port of Chancay, Lima, Peru - Villar-Valdez, Camila (2025)
Given that microplastics (MPs) are present in the aquatic environment, they are highly likely to be ingested by marine fish. Therefore, this study aims to determine the concentrations, characteristics (size, color, and shape), and types of MPs in the digestive tracts of two commercially important marine fish species (Ethmidium maculatum and Sarda chiliensis chiliensis; MA and BO, respectively) during three seasonal periods along the coast of Peru. Artisanal fishermen captured fish between November 2022 and November 2023 at the Port of Chancay, Lima, Peru. Laboratory digestion and microscopy techniques were used to identify, quantify, and characterize MPs in the fish. Results show a similar concentration across the three seasonal periods for BO (BO1= 12.2 ± 9.24 MPs/fish; BO2=10.73 ± 7.10 MPs/fish; BO3=8.73 ± 4.73 MPs/fish) and for MA (MA1=10 ± 7.71 MPs/fish; MA2= 4 ± 3.02 MPs/fish; MA3= 3.8 ± 1.78 MPs/fish). MPs' predominant colors were black and blue, predominant shapes were fibers and fragments, and predominant size range was from 1 mm to 5 mm. Finally, chemical analysis of MPs revealed the presence of polyethylene (PE) and polypropylene (PP). It is concluded that MPs were present in 100% of the MA and BO specimens.